Effects of Preform Shear on Tensile Properties of a Woven C/SiC Composite1. Issue 9 (23rd May 2016) - Shaw, John H.; Rossol, Michael N.; Marshall, David B.; Zok, Frank W.
Abstract : This article addresses effects of weave defects in an angle‐interlock C‐fiber preform on the tensile properties of the resulting fully processed C‐fiber/SiC‐matrix composite. For this purpose, a preform was intentionally sheared in a controlled manner after weaving. The resulting distortions were quantified by analyzing high‐resolution images of the preform surface after the first step of matrix processing, while the tows were still clearly visible. Comparisons are made of tensile test results on specimens cut from this composite panel and from a pristine panel in select loading orientations. Strain maps obtained by digital image correlation are used to identify local strain variations that are attributable to weave defects. The results are discussed in terms of: (i) the shear‐normal coupling that arises in loading orientations of present interest, and (ii) the geometric effects of tow misalignment on tow continuity along the specimen gauge length. The composite is found to perform in a robust manner, in the sense that the tensile properties are not sensitive to the presence of the defects.